THE ROLE OF LEMBAGA OMBUDSMAN DIY IN SURVEILLANCE PROBLEMS OF ACCEPTANCE OF NEW STUDENTS (PPDB) FOR 2020/2021 ACADEMIC YEAR IN THE PANDEMIC OF COVID-19 - Laksono, Praditio Dwi (Fakultas Ilmu Pendidikan, 2023)
This study aims to explain and describe the duties, authorities, functions and principles of the Ombudsman Institute Special Region of Yogyakarta (LO DIY) and their role in monitoring the implementation of PPDB TA. 2020/2021 during the COVID-19 Pandemic then What steps were taken by the Ombudsman Institute Special Region of Yogyakarta (LO DIY) in following up on incoming reports regarding the implementation of PPDB TA. 2020/2021 during the COVID-19 Pandemic and describes the results of the follow-up to the complaint.This research is a descriptive research with a qualitative approach. The subjects of this study were members of the DIY Ombudsman Institute and the DIY Community who experienced problems in the process of New Student Admission (PPDB). This research was conducted from January to March 2021 at the Ombudsman Institute for the Special Region of Yogyakarta. Data collection is done by using the method of Interview, Observation and documentation. The data analysis technique uses the Miles and Huberman model, namely data condensation, data display and conclusions drawing/verification.The results of the research show that the role of the DIY Ombudsman Institute has been operating as a supervisory institution that is directly responsible to the Governor, some of the roles of LOD include establishing complaint posts in the education sector since the Admissions of New Students (PPDB) T.A 2020/2021. Conduct studies on education regulations and/or policies issued by the Central Government up to the level of education units and/or universities. Conduct an assessment of the readiness of implementing learning for the new 2020/2021 school year starting from early childhood education to tertiary institutions. Follow up on complaints from the public. Monitor and supervise the implementation of learning for the new school year 2020/2021. Encouraging the synergy of all education stakeholders to implement learning adjustments in the new normal period for the 2020/2021 school year. The final product of LO DIY is LPK and recommendations. Recommendations issued by LO DIY do not have legally binding force but have morally binding force.